Comparing of Students\' Academic Achievement of Service Commitment Quota with other Quotas in Kashan University of Medical Sciences in the Academic Year 2021 - Ali Shafiei; Atefe Razaghi Zare Bidgoli; Gholamabbas Mousavi; Fakhrosadat Mirhosseini (مجله ایرانی آموزش در علوم پزشکی, 2023)
Introduction: Regarding the relationship between students' academic progress and their performance after graduation and considering the important role of entrance quota to the university in the academic progress of students, this study was designed to compare the academic progress of students of the service commitment quota with other quotas in Kashan University of Medical Sciences.